Rodent models of diet-induced type 2 diabetes mellitus: a literature review and selection guide - Engel, Holger; Xiong, Lingyun; Hirche, Christoph (Diabetes & metabolic syndrome, 2018)
Several research teams have focused on finding the “ideal” animal model that reflects the pathophysiological changes and closely simulates the metabolic characteristics of patients with type 2 diabetes. However, the multitude of studies on this topic has resulted in large variations, making the models difficult to compare, as the measured parameters vary significantly. Additionally, selecting the appropriate animal model for a new study has become more difficult due to the increasing number of background variables. This article gives a detailed overview of the literature, covering the entire range of animal models and model characteristics, and most importantly, provides guidance for selecting the most suitable model for specific research goals in the future.